Re-exploring democratic education through virtual learning communities - Tuğba ÖZTÜRK Hayriye (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Democratic pedagogy has been a concern in education for over a century. Although it has been interpreted in a variety of ways in different epochs, the main underpinning values have remained the same throughout the century. Now, in the information age, there has been considerable debate over whether the technology facilitates the democratization of education. With regard to this, in this article, in the first place, it was aimed to present the democratic education in a historical context, and then the virtual learning communities as a model which has the potential in democratizing the education was discussed. In doing this, a neutral approach was taken and pedagogical challenges were discussed. In reexploring the concept of democratic education, a critical in-depth literature review was taken in an emergent area of educational technology